Electrodeposition and Characterization of Nanocrystalline Ni-Mo Catalysts for Hydrogen Production. (21st February 2012) - Halim, J.; Abdel-Karim, R.; El-Raghy, S.; Nabil, M.; Waheed, A.
Abstract : Ni-Mo nanocrystalline deposits (7–43 nm) with a nodular morphology were prepared by electrodeposition using direct current from citrate-ammonia solutions. They exhibited a single Ni-Mo solid solution phase. The size of the nodules increased as electroplating current density increased. The molybdenum content—estimated using EDX analysis—in the deposits decreased from about 31 to 11 wt% as the current density increased from 5 to 80 mA·cm −2 . The highest microhardness value (285 Hv) corresponded to nanodeposits with 23% Mo. The highest corrosion resistance accompanied by relatively high hardness was detected for electrodeposits containing 15% Mo. Mo content values between 11 and 15% are recommended for obtaining better electrocatalytic activity for HER.